The Local Government Reformulation On Village Fund Supervision - Mohamad Sigit Ibrahim (Estudiante Law Journal, 2020)
The purpose of this research is to figure out the reformulation of village fund supervision by the local governments of Gorontalo District. The method employs empirical legal research that sets field facts as the research data. The data sources are primary data, namely field data, and secondary data consisting of documents, scientific papers, and other relevant secondary materials. Techniques of data collection are interviews and direct observation in the field. Findings reveal that the Gorontalo District Inspectorate, as the local government, carries out its duties and functions in supervising village funds through the method of auditing, reviewing, evaluating, monitoring, and other supervisory activities. However, the reformulation of village fund supervision has not been fully implemented due to several reasons, including the procedures of village fund supervision that have not been fully compliant with the internal audit standards of the Indonesian Government (SAIPI); time limit of the supervision; the limited number of governinent internal supervisory apparatus (APIP) in comparison with the number of villages to be supervised.